The achievement of the Te, div feedback control by CD4 seeding on EAST. (27th August 2021) - Wu, K; Yuan, Q; Xu, G; Wang, L; Eldon, D; Li, K; Liu, X; Meng, L; Zhang, L; Wang, Y; Duan, Y; Chen, M; et al.
Abstract: A multi-function divertor feedback control system has been built on Experimental Advanced Superconducting Tokamak (EAST) to treat the divertor heat load issue. With the real-time data of the Langmuir probes and the impurity seeding, the divertor electron temperature ( T e, div ) is well controlled to achieve the partial detachment phase. The first trial of the CD4 seeding for the T e, div reduction has been achieved on EAST long-pulse discharge. In the seeding phase, the T e, div was maintained close to 5 eV, and the surface temperature of the target plate ( T surface, div ) had a reduction of about 150 °C. The plasma stored energy had a reduction in the control phase, so it is necessary to find a way to keep the good plasma confinement in the next step. The CD4 injection also mitigated the low hybrid wave coupling rate in some degree. The big volume of the CD4 injection lifted the Greenwald density fraction from ∼0.4 to ∼0.7, which made the SOL into high recycling state. Most of the injected carbon particles were in the high ionized state, and with the lower of the T e, div, the tungsten line emission was suppressed obviously.